Application of a novel nanoemulsion adjuvant for rabies vaccine which stabilizes a Krebs cycle intermediate (SDH) in an animal model - Liu Ze; Li Zonglin; Wu Ya'Nan; Song Shaohui; Yang Huijuan; Cai Wei; Weidong Li; Guoyang Liao (Taylor & Francis Group, 2019)
Rabies is the most lethal zoonotic, vaccine-preventable viral disease in the world. Its treatment is complicated by insufficient vaccine supply and the requirement for four to five repeated injections, as commercially available inactivated rabies lack adjuvant and have low immunogenicity. In this study, we focused on the role of a Krebs cycle intermediate, succinate dehydrogenase (SDH), in the innate immune response to cytokine production. We formulated a novel nanoemulsion adjuvant, Golden03, which stabilizes mouse SDH activity and contains more coenzyme Q10 and succinic acid than the classic MF59 adjuvant. Mice were immunized on days 1, 3, and 7, with seroconversion rate results suggesting that Golden03 significantly enhanced vaccine-stimulated antibody production against the rabies virus. Neutralizing antibody concentration testing by RFFIT indicated that treatment with Golden03 could result in antibody levels of up to 0.74 IU/mL 5 days post infection (DPI). ELISPOT for IFN-γ in mouse spleen cells showed that Golden03 enhanced immune responses at 14 DPI, inducing a rapid and powerful cellular response compared to the control group. Furthermore, the Vaccine-Golden03 group displayed no obvious weight loss or death after intracranial injection with CVS-11. An additional advantage is that Golden03 allowed for a three-quarter reduction in dose, while maintaining its efficacy and rapid stimulation effect. We suggest that Golden03 could be developed as a potential adjuvant for use in human rabies vaccine.